Transmission Effectivity of Rice Yellow Stunt Disease by Imidacloprid-Resistant and Susceptible Brown Plant Hopper - Selgita Fitrian Kusumaningrum; Sri Sulandari; Y. Andi Trisyono; Sedyo Hartono (Universitas Gadjah Mada, 2021)
The brown plant hopper (BPH) is a major pest of rice and as a vector of Rice ragged stunt virus (RRSV) and Rice grassy stunt virus (RGSV). Curently, numerous rice yellow stunt disease symptoms are found in the field that caused by the single and simultaneous infection of these two viruses. Brown plant hopper population correlate with the incidence and severity of the disease. Misuse of insecticides, would cause of BPH resistances to imidacloprid. This study aimed to investigate the ability of BPH imidacloprid-resistant and susceptible to transmit of rice yellow stunt disease on rice plants. The variables tested were the acquisition period, inoculation period, number of infesting BPH, and lifespans of the viruliferous BPH that used in this research. Experiments were set as separated Completely Randomized Design with 10 replications for each treatment within an experiment. The results showed that both resistant and susceptible BPH to imidacloprid was able to transmit the virus to healthy plants. The acquisition and inoculation period test showed the BPH could transmit the virus with the shortest acquisition time for 30 minutes followed 24 hours of inoculation, as well as the acquisition time of 10 days with the shortest inoculation time for 30 minutes. Based on the incubation time, symptoms variation, and disease severity, susceptible BPH were more effective in transmitting rice yellow stunt disease than imidacloprid-resistant BPH. Single imidacloprid-resistant or susceptible BPH was proven able to transmit rice yellow stunt disease to healthy plants during its lifespan. Lifespans BPH viruliferous of imidacloprid-resistant were shorter than susceptible, which was 16 days for resistant BPH and 21 days for susceptible BPH.